2021
DOI: 10.3390/ijerph18189844
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Patient Empowerment and Nurses’ Use of Digital Strategies: eSurvey Study

Abstract: Patient empowerment is seen as the capability to understand health information and make decisions based on it. It is a competence that can improve self-care, adherence and overall health. The COVID-19 pandemic has increased the need for information and has also reduced the number of visits to health centers. Nurses have had to adapt in order to continue offering quality care in different environments such as the digital world, but this entails assessing the level of their patients’ empowerment and adapting mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
(76 reference statements)
1
12
0
1
Order By: Relevance
“…More than 50% of professionals over 30 use what they learned in the course every day compared to 6.66% of the youngest professionals. These data could reaffirm what other studies have suggested; nurses and younger healthcare professionals use fewer digital resources with their patients [ 3 , 29 ]. As reported by these studies, this could be due, in the case of nurses, to a generation gap or to a lack of training received by younger nurses during their undergraduate studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…More than 50% of professionals over 30 use what they learned in the course every day compared to 6.66% of the youngest professionals. These data could reaffirm what other studies have suggested; nurses and younger healthcare professionals use fewer digital resources with their patients [ 3 , 29 ]. As reported by these studies, this could be due, in the case of nurses, to a generation gap or to a lack of training received by younger nurses during their undergraduate studies.…”
Section: Discussionsupporting
confidence: 81%
“…Few healthcare professionals generate digital resources such as videos, blogs, infographics, and podcasts [ 3 ]. However, they are powerful tools for the follow-up of people with chronic pathologies [ 4 ], which can be a privileged scenario to understand better the needs and interests of people.…”
Section: Introductionmentioning
confidence: 99%
“…To efficiently promote mobile apps as a health education tool, hospitals need to train doctors, nurses, and patients on how to use these platforms for educational purposes [ 35 ]. Thanks to mobile apps, doctors can interact more often with patients, especially with those suffering from chronic diseases [ 37 ], and nurses can monitor patients’ medical outcomes more efficiently [ 38 ]. On the other hand, patients using mobile apps become more autonomous and participate more actively in collective decision-making processes concerning their health, which positively influences their medical outcomes [ 35 ].…”
Section: From Patients’ Education To Health Education Based On Mobile...mentioning
confidence: 99%
“…The nurses’ professional expertise and their close relationship with patients make them responsible for educating patients to develop a suitable lifestyle and empowering them through various methods. This is especially the case for the ones suffering from chronic diseases 21…”
Section: Introductionmentioning
confidence: 99%